Alkaloids from aerial parts of Houttuynia cordata and their anti-inflammatory activity. Issue 12 (15th June 2017) - Ahn, Jongmin; Chae, Hee-Sung; Chin, Young-Won; Kim, Jinwoong
Graphical abstract: Abstract: New alkaloids, houttuynamide B and C (1, 2 ) and houttuycorine (14 ), were isolated from the aerial parts of Houttuynia cordata Thunb. in addition to eighteen known alkaloids. Their structures were elucidated through extensive spectroscopic analysis. All the isolates were tested for their inhibitory activity against NO production in RAW 264.7 cells stimulated by LPS. Of the tested compounds, compound15 showed the most potent anti-inflammatory activity with an IC50 value of 8.7 μM.